Corrosion of Al(Co)CrFeNi High-Entropy Alloys - Godlewska, Elżbieta M.; Mitoraj-Królikowska, Marzena; Czerski, Jakub; Jawańska, Monika; Gein, Sergej; Hecht, Ulrike (Frontiers in Materials, 2020)
High-entropy alloys, AlCrFe2Ni2Mox (x = 0.00, 0.05, 0.10, and 0.15), AlCoCrFeNi, and two quinary alloys with compositions close to its face-centered cubic and body-centered cubic component phases, are tested for corrosion resistance in 3.5 wt% NaCl. The materials with different microstructure produced by arc melting or ingot metallurgy are evaluated by several electrochemical techniques: measurements of open circuit voltage, cyclic potentiodynamic polarization, and electrochemical impedance spectroscopy. Microstructure, surface topography, and composition are systematically characterized by scanning electron microscopy and energy-dispersive x-ray spectroscopy. The results indicate that minor additions of Mo positively affect corrosion resistance of the AlCrFe2Ni2 alloy by hampering pit formation. The face-centered cubic phase in the equimolar alloy, AlCoCrFeNi, is proved to exhibit more noble corrosion potential and pitting potential, lower corrosion current density and corrosion rate than the body-centered cubic phase. Overall behavior of the investigated alloys is influenced by the manufacturing conditions, exact chemical composition, distribution of phases, and occurrence of physical defects on the surface.